Micro e ultrafiltração como pós-tratamento para reúso de efluentes de abatedouro e frigorífico de suínos - Fappi, Devanir André (2015)
The food industry uses large volumes of water to meet the demand processes. Because of this, there is a large volume of generated waste that need to be addressed to ensure proper final destination. In view of the growing scarcity of water, the use rationalization of procedures of the water and the reuse of treated effluent arise as solutions to these problems. Application of separation processes by membranes in the treatment of wastewater for reuse food industry presents itself as an appropriate advanced treatment process. Thus, the aim of this study was to evaluate the use of membrane separation processes as advanced treatment of agroindustrial wastewater stemmed from a swine slaughterhouse, the western region of Paraná, aiming at the possibility of recycling these effluents. For this it was necessary: to define the physical-chemical characterization of the agro-industrial effluents; evaluate the use of microfiltration, ultrafiltration, microfiltration and ultrafiltration then under different conditions of pressure applied to the membrane, and evaluate the quality of the effluent obtained by separation processes with membranes, considering the care of the technical, legal and health requirements for different uses industrial. The results showed that membrane separation processes presented in a general way a considerable improvement in final effluent quality compared with the current tertiary treatment system used by the industry (physicochemical flotation) which promotes removal efficiencies in oscillating ranges from 3% to 29%, 44% to 70%, 40% to 46%, 50% to 58.5%, approximately, for the parameters: total volatile solids, turbidity, ammonia nitrogen and COD, respectively. Microfiltration had the following removal efficiency ranges, approximate: total volatile solids (51% - 64%), turbidity (83% - 99%), ammonia nitrogen (21% - 24%) and COD (64% - 72%). Ultrafiltration showed the following removal efficiency ranges, approximate: total volatile solids (23% - 51%), turbidity (87% - 99%), ammonia nitrogen (54% - 69%) and COD (77% - 85%). The completion of the test microfiltration followed by ultrafiltration under the best experimental conditions investigated achieved satisfactory results in the removal of approximately 97% for the turbidity, 17% total volatile solids, 67% for COD, 38% for ammonia nitrogen, 96% to 99.95% for thermotolerant and 93 to 99.69% for the heat-resistant coliforms coliforms. With increasing pressure to microfiltration and ultrafiltration permeate flux was increased and better quality of the final effluent. Although the effluents have provided separate permeate flow rates, very similar performance curves were obtained, characterized by a drop in permeate flux during the first minute filtration followed by a period where there is a gradual decline, with a tendency toward equilibrium. According to the physicochemical requirements and minimum microbiological required for the reuse of treated wastewater, microfiltration and ultrafiltration attended some of the monitored parameters, achieving the required quality for reuse in cooling towers, floor washing, irrigation of green areas , washing vehicles, fire protection and sanitary discharge.